Jacques Derrida e il non fenomenologico - Resta, Caterina (Bollettino Filosofico, 2018)
From its very first steps, Derrida’s thought engages a close confrontation with Husserlian phenomenology in order to take distance from it. My thesis is that, in spite of a claimed “fidelity” to phenomenological method, Derridian thought of différance has as its own preferential critical target phenomenology itself, intended as thought of the living present, of presence and of evidence. Starting from this thesis, deconstruction may be read first of all as deconstruction of phenomenology. It shows the irreducible character of the “non-phenomenological,” which every phenomenology tries to conceal as its own limit, as testified by Derrida’s analysis of gift and secret. These belong to the thought of sur-vival, which reveals death – the non-phenomenological par excellence – in the heart of life.